2013
DOI: 10.5194/hess-17-4001-2013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological modelling of a slope covered with shallow pyroclastic deposits from field monitoring data

Abstract: Abstract.A one-dimensional hydrological model of a slope covered with pyroclastic materials is proposed. The soil cover is constituted by layers of loose volcanic ashes and pumices, with a total thickness between 1.8 m and 2.5 m, lying upon a fractured limestone bedrock. The mean inclination of the slope is around 40 • , slightly larger than the friction angle of the ashes. Thus, the equilibrium of the slope, significantly affected by the cohesive contribution exerted by soil suction in unsaturated conditions,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 35 publications
4
61
1
Order By: Relevance
“…Greco and Bogaard (2016) give an example of the possible inclusion of slope hydrological processes in the definition of landslide initiation thresholds for the case of a slope covered by loose granular volcanoclastic deposits overlying a fractured limestone bedrock. The hydraulic characteristic curves of the volcanic ashes constituting the majority of the soil cover were known (Damiano et al, 2012;Greco et al, 2013), as well as the moisture state of the cover before all 78 observed rainfall events (Comegna et al, 2016). Hence, it was possible to define non-dimensional variables by comparing the meteorological triggers with the infiltration and storage capacity of the soil cover.…”
Section: Hydrological Interpretation Of Id Thresholdsmentioning
confidence: 99%
“…Greco and Bogaard (2016) give an example of the possible inclusion of slope hydrological processes in the definition of landslide initiation thresholds for the case of a slope covered by loose granular volcanoclastic deposits overlying a fractured limestone bedrock. The hydraulic characteristic curves of the volcanic ashes constituting the majority of the soil cover were known (Damiano et al, 2012;Greco et al, 2013), as well as the moisture state of the cover before all 78 observed rainfall events (Comegna et al, 2016). Hence, it was possible to define non-dimensional variables by comparing the meteorological triggers with the infiltration and storage capacity of the soil cover.…”
Section: Hydrological Interpretation Of Id Thresholdsmentioning
confidence: 99%
“…The role played by the possible interaction of the unsaturated cover with the underlying groundwater, through an impervious soil-bedrock interface, has also been analyzed, by Greco et al (2013), for a slope similar to those in Sarno.…”
Section: Description Of the Landslide Eventsmentioning
confidence: 99%
“…The limit equilibrium method or infinite slope stability approach is frequently integrated with Richards' equation (Lanni et al, 2013;Ng and Shi, 1998;Godt et al, 2008;Shuin et al, 2012;Wilkinson et al, 2002;Talebi et al, 2008;Greco et al, 2013) or conceptual models (Arnone et al, 2011;Simoni et al, 2008;Qiu et al, 2007) for landslide hazard evaluation. The limit equilibrium method and infinite slope approach assume or search for a potential failure surface.…”
Section: Introductionmentioning
confidence: 99%